Designing Composite BaCe0.4Zr0.4Y0.1Yb0.1O3-δ-Sm0.2Ce0.8O2-δ Heterostructure Electrolyte for Low-Temperature Ceramic Fuel Cell (LT-CFCs) - Wei Wei; Naveed Mushtaq; Yuzheng Lu; M. A. K. Yousaf Shah; Ligang Ma; Senlin Yan (Crystals, 2022)
In recent years, tuning perovskite and fluorite-based materials and modifying them to ionic conductors has been an interesting but challenging topic for advanced low-temperature ceramic fuel cells (LT-CFCs). In this regard, we prepared a new composite heterostructure, BaCe0.4Zr0.4Y0.1Yb0.1O3-Sm0.2Ce0.8O2 (BCZYYb-SDC), and evaluated it as an electrolyte to realize the fuel cell reaction. The developed electrolyte could be a hybrid ionic conductor, possess a very small ohmic area-specific resistance, and exhibit excellent fuel cell performance of over 1.0 W/cm2 along with higher OCV of more than 1.1 V at a low operating temperature of 550 °C. The attained performance and ionic conductivity are specially accredited to constructing the heterostructure of BCZYYb-SDC. Moreover, various spectroscopy and microscopic analysis methods have been used to investigate the ions’ transportation, while on the other hand suppressing the electronic conduction. The developed composite heterostructure proposes and suggests new insight to design new electrolytes for LT-CFCs.